Intraperitoneal meshes and adhesions: Estudio comparativo: polipropileno vs. poliglactina 91 O - Fernández Naone, G; Andreoli, G; Mayol, A.; Riveiro, M; Crestanello, J; Estrugo, R (Cirugía del Uruguay, 1991)
The authors make a prospective and paired study of plastic-adherential reaction to two intraperitonea/ prostheses. 20 mongrel dogs used as laboratory animals were operated by median laparotomy. A polypropylene mesh was col/ocated on the right and a polyglactin 910 one on the left, in the deep tace of the anterior parietal peritoneum. The presence and firmness of visceral adherences for each mesh was analysed. The results, analysed with J test, show significant differences in adherence formation and firmness for each mesh; they were more frequent and firm for polypropylene.